Executive Functioning Outcomes Over 6 Months of Atomoxetine for Adults With ADHD: Relationship to Maintenance of Response and Relapse Over the Subsequent 6 Months After Treatment. Issue 3 (February 2020) - Adler, Lenard A.; Solanto, Mary; Escobar, Rodrigo; Lipsius, Sarah; Upadhyaya, Himanshu
Objective: This study examines the relationship between maintenance of improved executive functioning (EF) in adults with ADHD with long-term symptom improvement with atomoxetine.Method: Data were collected from a yearlong, double-blind, placebo-controlled clinical study on adult patients with ADHD receiving atomoxetine (80-100 mg/day) for 24 weeks. Patients were then randomized to continue atomoxetine or placebo for 6 months. Executive functioning was rated with Behavior Rating Inventory of Executive Function–Adult Version: Self-Report™ (BRIEF-A: Self-Report™), and the T -scores were determined.Results: Postrandomization T -scores for atomoxetine patients were significantly better than those of placebo patients (3 and 6 months postrandomization). Patients with greater improvements in EF were more likely to show worsening of EF and to relapse after atomoxetine discontinuation. The maintenance of improved EF was significantly associated with improved ADHD symptoms (Conners' Adult ADHD Rating Scale–Investigator Rated: Screening Version [CAARS-Inv:SV] with adult prompts).Conclusion: Treatment with atomoxetine improved EF during the treatment phases. Improved EF was maintained up to 6 months after discontinuation of atomoxetine.